PELATIHAN PENERAPAN TEKNOLOGI IRIGASI TETES SEDERHANA UNTUK MEMPRODUKSI BUAH SALAK GULA PASIR DI LUAR MUSIM - RAI, IN; WIRAATMAJA, IW; SEMARAJAYA, CGA; ASTAWA, ING; SUKEWIJAYA, IM; MAYADEWI, N ARI; WIJANA, G (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015)
Natural flowering of “Salak Gula Pasir” occures once every three months or 4 times a year, however, only one to two of flower season succeeds to become fruit. Failure fruit-set causes the fruit harvest seasonally; partly due to the internal water content of leaf is low. The situation is not favorable in terms of agribusiness because production quantities accumulate only during the harvest time (on-season). Off-season flowering technology of “Salak Gula Pasir” by simple dripping irrigation has been founded, gardeners, however have not yet recognised. The aim of this community service is to introduce that technology by means of training to the gardeners. The participants attended the training seriously because the subject was really expected by them. After training, participants were convinced that they can do how to make off-season production of “Salak Gula Pasir”, moreover they expect the local government would provide rainwater harvesting and the required dripping irrigation installations. Keywords: salak Gula Pasir, drip, irrigation, off-season, training.